Evaluation and Maintenance of Behavioral Interventions for 22q11.2 Deletion Syndrome. (3rd April 2022) - Busch, Louis; Saini, Valdeep; Karim, Sidrah; Jones, Roland
ABSTRACT: 22q11.2-deletion syndrome is a genetic disorder caused by a small deletion of chromosome 22. This deletion often results in developmental delays, learning disabilities, medical conditions, and comorbid psychiatric conditions. Patients with 22q11.2DS may present with a variety of behavioral phenotypes including obsessiveness and rigidity, poor social skills, and anxiety. In some cases, the phenotype can consist of destructive and inappropriate behavior including harming self and others. Behavioral difficulties are reported as one of the most challenging aspects of 22q11.2-deletion syndrome for families of patients, however, few studies have examined behavioral interventions as a possible therapeutic treatment for this population. Using principles derived from operant-behavioral psychology, we conducted functional assessments to determine the environmental correlates of destructive and inappropriate behaviors in two adult men with 22q11.2-deletion syndrome. Subsequently, behavioral interventions based on differential reinforcement were incorporated into each participant's natural environment to eliminate these behaviors. Significant reductions in destructive and inappropriate behavior were observed with both participants and therapeutic gains were maintained at follow-up. We discuss the role of behavioral interventions in combination with appropriate psychotropic medication when addressing challenging behaviors in this population.